Isolasi Mikroba Endofitik dari Tumbuhan Quisqualis indica L. dan Uji Potensinya dalam Menghasilkan Senyawa Antimikroba - Priyo Wahyudi; Mochamad Hendriana (JURNAL ILMU KEFARMASIAN INDONESIA, 2003)
Endophytic microbe is a definition which is given to all microorganisms that during a more or less long period of their life, colonize symptomnlessly the living tissues of their hosts. The endophytes can produce useful substances such as oligosaccharide degrading enzyme, antimicrobial substances and plant growth regulator. Quisqualis indica is one of tropical herb that is widely known for traditional medicine. There is no information about endophytic microbes of this plant. The aim of this study are to isolate the endophytic microbes from Q. indica, and screen on their ability in producing antimicrobial substances. Isolation is conducted by direct seed plating method using PDA and NA medium. Liquid fermentation method is taken place using supernatant F4 and PDY medium, then followed by bioassay of the supernatant on three test microbes: Staphylococcus aureus, Escherichia coli and Candida albicans. Result of isolation is 25 bacterial isolates and 12 fungal isolates. Result of bioassay showed that there are some isolates that have ability in producing antimicrobial substances. There are 1 bacterial isolate and 2 fungal isolates that showed wide spectrum activity of antimicrobial substance.